Presence of malaria parasitaemia among patients presenting with fever or selected non-specific symptoms to medical institutions and malaria mobile clinics in Vavuniya district and to describe some factors associated with parasitaemia. - Jegathambikai, J (My University, 2006)
Clinical immunity to malaria was studied by testing for presence of malaria parasitaemia among 1204 patients presenting either with fever or with selected non-specific symptoms, to different types of clinics (i.e. government medical institutions, private medical clinics and malaria mobile clinics), in a district in Northern Sri Lanka, which is endemic for malaria. All the patients were subjected to microscopic examination for malaria parasite. A sample of patients was tested by Dipstick method also at recruitment. Socio-demographic information of the patients was obtained using an interviewer administered questionnaire. During the 6-month period of the study only 26 malaria positive patients were identified. All identified malaria positives were P. vivax cases. Considering the age distribution of positives cases, there is significant reduction in the number of malaria cases with increase in age (pO.OOI). The highest proportion of cases were found among the 1-10 year age group. and no cases were detected among those over 50 years of age When considering the duration of stay, people who had malaria (confirmed by microscopy) had been living in Vavuniya district for lesser number of years when compared to those who had no malaria .